Development of E-Modules To Improve Students' Problem Solving Abilities on Ethnoscience Integrated Colloidal Material with the Problem Based Learning Model - Iriani*, Rilia; Risna, Risna; Bakti, Iriani; Saadi, Parham; Abrori, Fadhlan Muchlas; Leny, Leny (Universitas Syiah Kuala, 2024)
Research has been carried out on the development of e-modules to improve student problem solving on ethnoscience integrated colloidal material using the problem based learning model. This study aims to determine the validity, practicality, and effectiveness of the e-modules developed. This research is a research development research with the ADDIE model (analysis, design, development, implementation, and evaluation). The subjects of this study were 5 validators and 33 students of grade XI MIPA 5 SMA Negeri 2 Banjarmasin. Data collection using test and non-test instruments (questionnaires and observation sheets). Data analysis using descriptive techniques. The results of this study show that this e-module is very valid, very practical, and effective. The N-Gain value is 0.89 in high category, which is that this colloidal e-module is able to improve problem solving capabilities.